Avaliação da atividade antiedematogênica, antinociceptiva e toxicidade de Myrcia amazonica D.C. (Myrtaceae) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
Medicinal plants are considered great importance for obtaining bioactive molecules and for drug discovery, and it is essencial to perform researches to assess their pharmacological and toxicological effects. Myrcia amazonica DC is popularly known as “pedra-ume-caá” in northern Brazil. It is used by the population for the treatment of various diseases such as diseases of inflammatory origin, diabetes and diarrhea. Although being used and sold in markets and fairs as a medicinal plant, there are no published researches about its real pharmacological and toxicological properties, and such studies are essential to ensure the efficacy and safety of plants traditionally used as medicinal. Thus, the aim of this study was to evaluate the antiedematogenic and antinociceptive activities of hydroalcoholic extract of M. amazonica leaves (EHAMa) at doses of 360, 480 and 600mg/kg, and to investigate its potential neurotoxic and hepatotoxic effects. The antiedematogenic activity was evaluated using the paw edema test induced by carrageenin and nociceptive activity by the writhing test induced by acetic acid. The possible neurotoxic effects of acute and subchronic treatment were investigated through the behavioral tests: the Morris water maze and rotating bar. The evaluation of hepatotoxicity was performed by quantitative determination of serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT). The results showed that the EHAMa acute administration (a.a.), significantly inhibited the paw edema induced by carrageenan at 600 mg / kg in 67%, compared with the control group, demonstrating that it has potential as an anti-inflammatory agent. The EHAMa (a.a.) showed analgesic effect in the doses 360, 480 and 600 mg/kg significantly reducing the number of writhes by 42, 40 and 97% respectively. The treatment, both acute and subchronic, with EHAMa at a dose of 600 mg / kg did not cause significant alterations on locomotion, memory and learning Wistar rats. The results for the levels of ALT and AST enzymes in the serum of mice have shown that the treatment for 21 days with EHAMa at a dose of 600 mg / kg had significant difference compared with the control group, in order to reduce the levels of these enzymes in 23% for AST and 42% for ALT, can thus suggesting a possible effect hepatoprotective well as the absence of hepatotoxic effects. These results indicate a pharmacological potential of EHAMa, which explains in part the use of this specie by the population. However, further studies are needed to know the active ingredients of the specie and its possible mechanisms of action.
Keywords: Pedra-ume-caá; Edema de pata; Contorções abdominais; Hepatoxicidade; Neurotoxicidade; CNPQ:: CIÊNCIAS BIOLÓGICAS; BIOPROSPECÇÃO DE RECURSOS NATURAIS DA AMAZÔNIA; ESTUDOS E MANEJOS DOS ECOSSISTEMAS AMAZÔNICOS